2018
DOI: 10.20944/preprints201807.0393.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphorylation-Dependent Inhibition of Akt1

Abstract: Akt1 is a proto-oncogene that is over active in most cancers. Akt1 activation requires phosphorylation at Thr308; phosphorylation at Ser473 further enhances catalytic activity. Akt1 activity is also regulated via interactions between the kinase domain and the N-terminal autoinhibitory pleckstrin homology (PH) domain. As it was previously difficult to produce Akt1 in sitespecifically phosphorylated forms, the contribution of each activating phosphorylation site to autoinhibition was unknown. Using a combination… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…MK‐801 also blocked the binding of Akt1‐PIAS1 (Figure S1B). The enzymatic activity of Akt1 is reported to be fully stimulated by both T308 and S473 phosphorylation 25,26 . We found that Bicuculline treatment increased Akt1 T308 phosphorylation, while relatively stable levels of S473 phosphorylation were maintained (Figure 1A).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…MK‐801 also blocked the binding of Akt1‐PIAS1 (Figure S1B). The enzymatic activity of Akt1 is reported to be fully stimulated by both T308 and S473 phosphorylation 25,26 . We found that Bicuculline treatment increased Akt1 T308 phosphorylation, while relatively stable levels of S473 phosphorylation were maintained (Figure 1A).…”
Section: Resultsmentioning
confidence: 73%
“…The enzymatic activity of Akt1 is reported to be fully stimulated by both T308 and S473 phosphorylation. 25,26 We found that Bicuculline treatment increased Akt1 T308 phosphorylation, while relatively stable levels of S473 phosphorylation were maintained (Figure 1A). These data implicate that NMDA receptordependent neuronal activity upregulates Akt1 SUMO1ylation mainly by PIAS3 and facilitates Akt1 activity by accelerating T308 phosphorylation.…”
Section: Nmda Receptor-dependent Neuronal Activity Induces Akt1 Sumoylationmentioning
confidence: 89%
See 1 more Smart Citation